Prognosis of long-term survival considering disease-specific death in patients with chronic myeloid leukemia - Pfirrmann, Markus; Saußele, Susanne; Hehlmann, Rüdiger (Leukemia, 2016)
In patients with chronic myeloid leukemia (CML), first-line imatinib treatment leads to 8-year overall survival (OS) probabilities above 80%. Many patients die of reasons unrelated to CML. This work tackled the reassessment of prognosis under particular consideration of the probabilities of dying of CML. Analyses were based on 2290 patients with chronic phase CML treated with imatinib in six clinical trials. ‘Death due to CML’ was defined by death after disease progression. At 8 years, OS was 89%. Of 208 deceased patients, 44% died of CML. Higher age, more peripheral blasts, bigger spleen and low platelet counts were significantly associated with increased probabilities of dying of CML and determined a new long-term survival score with three prognostic groups. Compared with the low-risk group, the patients of the intermediate- and the high-risk group had significantly higher probabilities of dying of CML. The score was successfully validated in an independent sample of 1120 patients. In both samples, the new score differentiated probabilities of dying of CML better than the Sokal, Euro and the European Treatment and Outcome Study (EUTOS) score. The new score identified 61% low-risk patients with excellent long-term outcome and 12% high-risk patients. The new score supports the prospective assessment of long-term antileukemic efficacy and risk-adapted treatment.